Spatial Impact of New Housing Trends in the Periphery of Istanbul Metropolitan Area - Tuba Inal Cekic; Ferhan Gezici (European Regional Science Association (ERSA), 2005)
Globalization had a significant effect on socio-economic and spatial changes in Istanbul as the largest city of Turkey following the trends in other cities of the world since the beginning of 1980. In this transformation process which the city center was dislocated and the land rapidly opened for new demands, while the construction sector flowed to business spaces like office blocks, department stores, and five-star hotels; construction companies that prospered ventured to major housing projects in the urban periphery. Therefore, high-income group left the city center due to low quality of life in inner-city areas caused by the drawbacks of rapid urbanization such as intensive residential areas, lack of open and green sites, traffic and parking problems, increasing crime rates. These high-income group housing areas which are brought a new sight as "gated communities”, mostly developed towards the north where the natural resources e.g. forest and water basin of Istanbul Metropolitan Area are located and became a new issue while squatter settlements are still concerned. However, they are planned as individual projects with their own security systems and modern comfortable components; they developed without integration to the metropolitan master plan. The aim of the paper is to examine locational preferences and planning process of high-income group housing projects and prove their effects on the transformation of urban periphery. Their effects on the land values and the role of the central and local governments on this process are examined. Furthermore, this paper attempts to make a contribution to the literature on gated communities by taking account of their spatial impacts. The main findings of paper put forward that existing high-income group housing projects became attraction points for new projects and affected on land use and transportation pattern, while becoming new threats for natural resources of metropolitan periphery.
Keywords: 330